Merits of bamboo utilization in earth preservation, water, and wastewater treatment : A mini review - Kuok, King Kuok; Muhammad Khusairy, Bakri; Chiu, Po Chan; Md. Rezaur, Rahman; Murtala, Namakka; Khairul Anwar, Mohamad Said; Chin, Mei Yun; Mohammed Muzibur, Rahman (Department of Forest Biomaterials at North Carolina State University, 2024)
This paper reviews the positive attributes and challenges of bamboo usage in carbon absorption, water, and wastewater purification. Bamboo can serve as a habitat for a variety of creatures and supports a diversified ecology. Bamboo roots can cast a fibrous net into the ground to prevent soil erosion and degradation. As the water passes through this woven mesh, the bamboo roots act as a filter, drawing toxins and other contaminants out of the water. Bamboo can treat wastewater effectively in free-water surface, horizontal flow, and vertical flow constructed wetlands. Bamboo charcoal has exceptional filtering properties for cleaner drinking water and better air quality. Additionally, bamboo can be used to form cellulose-based membranes. Bamboo is a renewable resource for creating paper, furniture, and building materials. Bamboo has various benefits. Thus, bamboo forests offer opportunities for rural communities to thrive economically.